(untitled) (The International Research Journal of Management Science, 2022)
Purpose: The primary goal of the study is to find out significant differences in the purchase of smartphones by gender, between age groups, and between income and education levels. This study also examines how demographics affect Nepalese users’ intentions to purchase smartphones, including gender, age groups, educational attainment, and income levels. Design/Methodology/Approach: Deductive research approach has been used in the study. The study used a descriptive research design. This study made use of primary data. 396 Smartphone users in Kathmandu were polled using a convenient sample technique through a Five-point Likert scale questionnaire. To make a diagnosis and come to reliable results, descriptive statistical analysis, independent sample t-tests, and one-way ANOVA have been used. To examine the association between these characteristics and purchase intention, gender, age groups, educational attainment, and income levels are considered independent variables. Findings: Therefore, it can be said that demographic parameters influence consumers’ purchase intention for Smartphones. Independent sample t-test and one-way ANOVA test results reveal that there is no significant difference in purchase intention for Smartphone buying between gender, age groups, levels of education, and levels of income. Originality/Value: Prior research studied the various factors influencing purchase intention, such as advertisement, country of origin, brand image, price, quality, reference groups, price, income, and personal characteristics. To the best of the authors’ knowledge, their research is the first to study the impact of age, gender, level of education, and income on the purchase intention of smartphones buying. Limitations/Implications: There are various factors influencing the purchase intention; among them, only demographic factors such as age, gender, level of education, and level of income are undertaken for the study. Only Smartphone products are taken in the study, and other products are excluded from the study. The study findings will be useful to Smartphone businesses to formulate marketing strategies and plans to increase consumers’ purchase intention and sales of the products.